Knowledge base for efl/esl educators: what does it mean? (2002)
Searching for an appropriate definition of what constitutes knowledge base in the teaching profession has become a central focus of attention for researchers, educators, and accreditation agencies during the last decades. The importance of clarifying such a definition has a double value. On the one hand it has become a determinant factor when assessing if teacher preparation programs are meeting the standards for excellence in education. On the other hand, the issue concerns prospective and experienced teachers themselves as they search for opportunities to acquire such knowledge whose ultimate goal is to improve the quality of their practice. But what exactly does this knowledge embrace and more specifically how does it influence an English language teacher? The purpose of this article is to present a synthesis of the most significant responses to these questions and to invite English language teachers to examine their knowledge framework in the hope that this reflection allows for an enrichment of their practice.